Native pigs: a climate resilient business enterprise - Rosales, Belina O; Palima, Carlo; Hernández, Gerry; Gonsalves, Julian Francis; Rosimo, Magnolia M.; Santiago, Rene; Vidallo, Rene R.; Locaba, Rico; Soksophors, Yim (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
The International Institute of Rural Reconstruction (IIRR) and CCAFS introduced the low external input project on small-livestock system to communities in Guinayangan Climate-Smart Village (CSV) in the Philippines. This is part of the Developing Scalable Approaches for Community Based Adaption project of IIRR. Climate-smart agriculture approaches, including those in livestock production, were introduced to help build farm resilience in anticipation of the impacts of climate change. The experiences shared in this publication was generated over 6 years. Replication are now seen in nearly all of the Philippine Department of Agriculture CSVs.